Nitrogen Use Efficiency and Carbon Traits of High-Yielding European Hybrid vs. Line Winter Wheat Cultivars: Potentials and Limitations - Prey, Lukas; Kipp, Sebastian; Hu, Yuncai; Schmidhalter, Urs (Frontiers in Plant Science, 2019)
In contrast to allogamous crops, hybrid wheat has only recently been fostered by breeding companies in Europe. Hybrid cultivars are often associated with higher stress resistance, e.g., under drought conditions, but little is known about the nitrogen (N) use efficiency of modern hybrid wheat cultivars. Therefore, four high-yielding European hybrid and nine line winter wheat (Triticum aestivum L.) cultivars were grown under three N regimes in a high-yielding German environment and compared over three years at anthesis and maturity for 53 direct and indirect traits of yield formation and N allocation. Dry matter and N uptake were determined on the plant and plant organ levels. Commercial heterosis, expressing the performance of hybrid in comparison to line cultivars, was positive for about one-third of the 53 direct and indirect N and carbon traits. On average, hybrid cultivars yielded more grain (+5.5%), mainly due to a higher harvest index (+3.5%) together with higher post-anthesis assimilation and more grains per spike. However, grain N content was lower for hybrids (-8.5%), so their grain N uptake was not higher. This went along with comparable trait values for N translocation and the temporal N uptake of the different plant organs. Current wheat hybrids seem to be more efficient in overall N use because they are better at converting (higher N utilization efficiency) comparable amounts of N uptake (N uptake efficiency) into grain biomass. The results suggest that given increased seed costs for hybrids, the yield advantage of hybrid cultivars over locally adapted line cultivars will have to be further increased for establishing hybrids in low-stress, high-yielding environments.